Psychometric characteristics of Brief COPE in a sample of at-risk families - Nunes, Cristina (2023)
Coping strategies are a relevant construct for assessing the family context, particularly in families at psychosocial risk. This study aimed to analyze the psychometric characteristics and factor structure of the Brief COPE, which measures coping strategies. Participants were 116 parents (80% women, age average = 35.30 years) with dependent children who had an active case with Child Protective Services in Algarve. Besides the Brief COPE, we also used a demographic questionnaire. Findings support retaining all 28 items and lend support to the 14-dimension of the original version, which obtained satisfactory levels of internal consistency. Despite some limitations, the psychometric properties found justify the use of this instrument with families at psychosocial risk.